2010
DOI: 10.1007/s11302-010-9186-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide on purinergic signalling in the cochlea

Abstract: In the inner ear, there is considerable evidence that extracellular adenosine 5′-triphosphate (ATP) plays an important role in auditory neurotransmission as a neurotransmitter or a neuromodulator, although the potential role of adenosine signalling in the modulation of auditory neurotransmission has also been reported. The activation of ligand-gated ionotropic P2X receptors and G proteincoupled metabotropic P2Y receptors has been reported to induce an increase of intracellular Ca 2+ concentration ([Ca 2+ ] i )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 131 publications
(150 reference statements)
0
7
0
Order By: Relevance
“…A cross talk between NO and ATP is suggested in the auditory signal transduction. 21 Our study showed that the noise-induced NO decrease may therefore affect hearing negatively. We need to prove this finding by checking NOS expression in these subjects in the future planning studies.…”
Section: Discussionmentioning
confidence: 59%
“…A cross talk between NO and ATP is suggested in the auditory signal transduction. 21 Our study showed that the noise-induced NO decrease may therefore affect hearing negatively. We need to prove this finding by checking NOS expression in these subjects in the future planning studies.…”
Section: Discussionmentioning
confidence: 59%
“…Additional examples of ATP-elicited production and release of NO include the cochlea [215] or the vascular system, where NO released from endothelium induces smooth muscle relaxation [216].…”
Section: Nitric Oxide Signalingmentioning
confidence: 99%
“…Prior to hearing onset, spontaneous Ca 2+ APs of IHCs are the result of ATP that is released from the organ of Kölliker and that drives small voltage input in IHCs after birth (Tritsch and Bergles 2010 ; Tritsch et al 2007 ; for a review, see Wang and Bergles 2014 ). ATP possibly activates IHCs through ligand-gated ionotropic P2X receptors or G-protein-coupled metabotropic P2Y receptors, both of which have been reported to induce increases of the intracellular Ca 2+ concentration ([Ca 2+ ] i ; Harada 2010 ). During the period of spontaneous Ca 2+ APs, the synaptic machinery of IHCs progressively evolves from multiple spherical bodies, typical of immature hair cells (Fig.…”
Section: Critical Maturation Steps Of Ihc Synapse Before Hearing Onsementioning
confidence: 99%